(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Nowadays, digital technologies are widely used in the educational process. In particular, games based on neuro technologies (neuro games) serve as an effective tool for developing key cognitive functions such as mental activity, attention, memory, and critical thinking in students. This thesis explores the types of modern neuro games, their impact on students’ cognitive abilities, and their integration into the learning process. The research justifies the role of neuro games in enhancing students’ learning motivation, independent thinking in problem-solving situations, and the ability to make quick and accurate decisions, based on experiments, observations, and surveys.